Management of acute type A aortic dissection in the elderly: an analysis from IRAD. (3rd January 2022) - Hemli, Jonathan M; Pupovac, Stevan S; Gleason, Thomas G; Sundt, Thoralf M; Desai, Nimesh D; Pacini, Davide; Ouzounian, Maral; Appoo, Jehangir J; Montgomery, Daniel G; Eagle, Kim A; Ota, Takeyoshi; Di Eusanio, Marco; et al.
Abstract: OBJECTIVES: We sought to examine management and outcomes of (Stanford) type A aortic dissection (TAAAD) in patients aged >70 years. METHODS: All patients with TAAAD enrolled in the International Registry of Acute Aortic Dissection database (1996–2018) were studied ( n  = 5553). Patients were stratified by age and therapeutic strategy. Outcomes for octogenarians were compared with those for septuagenarians. Variables associated with in-hospital mortality were identified by multivariable logistic regression. RESULTS: In-hospital mortality for all patients (all ages) was 19.7% (1167 deaths), 16.1% after surgical intervention vs 52.1% for medical management ( P  <   0.001). Of the study population, 1281 patients (21.6%) were aged 71–80 years and 475 (8.0%) were >80 years. Fewer octogenarians underwent surgery versus septuagenarians (68.1% vs 85.9%, P  <   0.001). Overall mortality was higher for octogenarians versus septuagenarians (32.0% vs 25.6%, P  =   0.008); however, surgical mortality was similar (25.1% vs 21.7%, P  =   0.205). Postoperative complications were comparable between surgically managed cohorts, although reoperation for bleeding was more common in septuagenarians (8.1% vs 3.2%, P  =   0.033). Kaplan–Meier 5-year survival was significantly superior after surgical repair in all age groups, including septuagenarians (57.0% vs 13.7%, P  <   0.001) and octogenarians (35.5% vs 22.6%, P  < 0.001). CONCLUSIONS: When compared with septuagenarians, a smaller percentage of octogenarians undergo surgical repair for TAAAD, even though postoperative outcomes are similar. Age alone should not preclude consideration for surgery in appropriately selected patients with TAAAD. Abstract : Despite reports that continue to demonstrate improvement, surgical mortality in (Stanford) type A acute aortic dissection (TAAAD) remains substantial [1, 2].